THE INFLUENCE OF WORK DISCIPLINE, EMOTIONAL INTELLIGENCE, AND WORK MOTIVATION ON THE PERFORMANCE OF PAUD TEACHERS IN PAMULANG, SOUTH TANGERANG - Kultsum, Ummi (BAIK Publishers, 2024)
The purpose of this study was to determine the effect of work discipline and emotional intelligence on the performance of PAUD teachers in Pamulang, South Tangerang. The research method used in this research is descriptive with a quantitative approach. The population amounted to 1,652 people, this study used a sampling technique with the accidental sampling method and obtained a total sample in this study of 50 respondents. Data analysis techniques using multiple linear regression. The results showed that: There is a positive and significant influence of work discipline and emotional intelligence variables on the performance of PAUD teachers in Pamulang, South Tangerang. This is evidenced by the value of Fhitung > Ftable, namely 72.591 > 2.70 with a probability value (significance) = 0.000 which is below 0.005.